Reproductive complications in celiac disease patients in Slovenia. (July 2019) - Pogačar, Maja Šikić; Vlaisavljević, Veljko; Turk, Eva; Mičetić-Turk, Dušanka
Abstract: Objective: Celiac disease is associated with higher risk of infertility, recurrent abortions, and adverse outcomes in pregnancy and in puerperium. The aim of the study was to analyse the association between celiac disease and reproductive disorders in the group of celiac patients and compare these to healthy controls. Methods: A retrospective case-control matched study. The association between celiac disease and menstrual cycle, gyneco-obstetrical complications was assessed with a questionnaire specifically developed for the study. 144 celiac women and 61 celiac men, members of Slovenian Celiac Society, together with 71 healthy women and 31 healthy men participated in the study. Results: A higher percentage of celiac women (27.1%) had difficulties in conception of the first child when compared to healthy controls (12.7%) (p = 0.042). In addition, celiac women experienced more complications than healthy controls during the pregnancy, such as abortions or intrauterine growth retardation (p < 0.005). In our study, the prevalence of reproductive problems was not the same in celiac males and females. Altogether 2 celiac men (3.3%) reported having fertility problems, however, the difference between male cases and controls was not statistically significant (p = 0.548). Conclusion: Physicians should examine women with unexplained infertility, recurrent abortions or intrauterine growth retardation for undiagnosed celiac disease. Compared with healthy women, women with celiac disease have increased risk of spontaneous abortions, preterm delivery and fewer successful pregnancies.